2020
DOI: 10.1038/s41598-020-60210-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial and lipid metabolism is a conserved effect of Insulin/PI3K pathway downregulation in adipose tissue

Abstract: The Insulin/IGF-1 signalling (IIS) pathway plays an essential role in the regulation of glucose and lipid homeostasis. At the same time, a reduction in the IIS pathway activity can extend lifespan and healthspan in various model organisms. Amongst a number of body organs that sense and respond to insulin/IGF-1, the adipose tissue has a central role in both the metabolic and lifespan effects of IIS at the organismal level. Genetic inactivation of IIS components specifically in the adipose tissue has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Genetic inactivation of the IIS pathway in Drosophila and C. elegans has been shown to extend their lifespans (Broughton et al, 2005;Clancy et al, 2001;Kenyon et al, 1993;Giannakou et al, 2004;Nässel et al, 2015). The phospho- (Bettedi et al, 2020), and downregulation by genetic modulation of the IIS pathway in invertebrates has been associated with prolonged lifespan (Tatar et al, 2003). Our results also revealed the increased lipid metabolism as a conserved effect of downregulating InR/PI3K pathway, as in ppl-Gal4>UAS-Pten flies.…”
Section: Quantifying Lipid Metabolism In Aging Drosophila Mutantssupporting
confidence: 57%
See 1 more Smart Citation
“…Genetic inactivation of the IIS pathway in Drosophila and C. elegans has been shown to extend their lifespans (Broughton et al, 2005;Clancy et al, 2001;Kenyon et al, 1993;Giannakou et al, 2004;Nässel et al, 2015). The phospho- (Bettedi et al, 2020), and downregulation by genetic modulation of the IIS pathway in invertebrates has been associated with prolonged lifespan (Tatar et al, 2003). Our results also revealed the increased lipid metabolism as a conserved effect of downregulating InR/PI3K pathway, as in ppl-Gal4>UAS-Pten flies.…”
Section: Quantifying Lipid Metabolism In Aging Drosophila Mutantssupporting
confidence: 57%
“…Further comparing lipid metabolism in each fly mutant during aging revealed that genetic downregulation of InR/PI3K pathway would maintain the relatively high lipid metabolism in flies ( ppl ‐ Gal4 > UAS ‐ Pten ) with aging (Figure S4c ), but upregulation ( ppl ‐ Gal4 > UAS ‐ InR del ) or inactivation ( ppl ‐ Gal4 > UAS ‐ InR DN ) of the pathway led to significant decreases of lipid metabolism in aged flies (Figure S4b,d ), similarly as in the control (Figure S4a ). A recent study on mouse adipose tissue and fly fat body showed that downregulation of InR/PI3K pathway increased lipid metabolism as a conserved effect (Bettedi et al, 2020 ), and downregulation by genetic modulation of the IIS pathway in invertebrates has been associated with prolonged lifespan (Tatar et al, 2003 ). Our results also revealed the increased lipid metabolism as a conserved effect of downregulating InR/PI3K pathway, as in ppl ‐ Gal4 > UAS ‐ Pten flies.…”
Section: Resultsmentioning
confidence: 99%
“…PI3Ks p110α and p110β have been pursued as therapeutic targets mainly in oncology [ 9 ]. However, inhibition of p110α has recently been shown to increase energy expenditure through potentiation of β-AR signalling and enhancement of mitochondrial activity in adipocytes [ 8 , 10 ]. The potentiating effect of p110α inhibition in β-AR signalling has also been shown in human adipose tissue [ 11 ].…”
Section: Introductionmentioning
confidence: 99%